PENGARUH SERVICE DIFFERENTIATION DAN REPUTASI TERHADAP KEUNGGULAN BERSAING UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Sipahutar, Robinson; Haloho, Elizabeth; Darus, Prabudi (Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine the influence of differential service and good reputation partially and simultaneously on the competitive advantage of Santo Thomas Catholic University, Medan. The population in this study was 6,540 active students for the 2022/2023 academic year. The sample in the study was 98 respondents using the Simple Random Sampling technique. The analytical methods used are instrument tests, classical assumption tests, hypothesis tests, coefficient of determination tests and multiple linear regression analysis. The research results show (1) Based on the Partial Test (t Test) Service differentiation has a positive and significant effect on the competitive advantage of Santo Thomas Catholic University Medan, (2) Based on the Partial Test (t Test) reputation has a positive and significant effect on the competitive advantage of Santo Thomas Catholic University Medan, and (3) Based on Simultaneous Test (F Test) Service differentiation and reputation simultaneously competitive advantage Santo Thomas Catholic University Medan.